Enjoyment, boredom, and perceived effectiveness of learners in language MOOCs: the mediating effect of self-regulated learning - Rong Luo; Yijin Wang (Frontiers in Psychology, 2023)
Self-regulated learning in technology-supported environments has attracted much scholarly attention in recent years. With the rapid expansion of online education, students’ emotions have also been studied extensively in second language acquisition. However, few empirical studies have examined the interrelationship between students’ self-regulated learning and emotions in the emerging field of language MOOCs (LMOOCs). This study bridged this gap by exploring the relationship between foreign language enjoyment (FLE), boredom (FLB), self-regulated learning (SRL), and perceived effectiveness in LMOOC learning. Data were collected among 356 successful learners of a language MOOC in mainland China through a cross-sectional study. The results showed that LMOOC learners had a high level of enjoyment and a moderate level of boredom. A significantly positive relationship was noted between FLE and SRL while a negative relationship was found between FLB and SRL. SRL was confirmed to be the mediator between FLE, FLB, and PE, which partially mediated the effects of FLE on PE and fully mediated the effects of FLB on PE. Perceived effectiveness was predicted by all SRL strategies and time management significantly predicted perceived effectiveness. The results provided pedagogical implications for students to develop positive emotions and effective SRL strategies to achieve better learning outcomes in LMOOC learning.